2005
DOI: 10.1016/j.chembiol.2005.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting RNA-Interference Pathway with Small Molecules

Abstract: RNA interference (RNAi) is a process whereby short-interfering RNAs (siRNA) silence gene expression in a sequence-specific manner. We have screened a chemical library of substituted dihydropteridinones and identified a nontoxic, cell permeable, and reversible inhibitor of the RNAi pathway in human cells. Biochemical and fluorescence resonance-energy transfer experiments demonstrated that one of the compounds, named ATPA-18, inhibited siRNA unwinding that occurred within 6 hr of siRNA transfection. Extracts pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 22 publications
0
30
0
1
Order By: Relevance
“…As shown by hybridization studies, duplexes aG2/as2Uall 19 bp (19), aG2/as2Uall 17 bp (20), and aG2/ as2Uall 15 bp (21) exhibit extremely high thermodynamic stability (the relevant melting profiles did not reach a plateau up to 96°C). We asked the question whether such stable duplexes can be effectively unwound by the dsRNA helicase engaged in the RISC complex (Chiu et al 2005). It has already been reported that thermodynamically stable duplexes containing LNA-modified units are active in RNAi-induced gene silencing (Braasch et al 2003;Elmen et al 2005), although their ethylene bridged nucleic acid analogs completely lost their silencing potency (Hamada et al 2002).…”
Section: Duplexes Of Various Lengths With Antisense Strands Fully Modmentioning
confidence: 99%
“…As shown by hybridization studies, duplexes aG2/as2Uall 19 bp (19), aG2/as2Uall 17 bp (20), and aG2/ as2Uall 15 bp (21) exhibit extremely high thermodynamic stability (the relevant melting profiles did not reach a plateau up to 96°C). We asked the question whether such stable duplexes can be effectively unwound by the dsRNA helicase engaged in the RISC complex (Chiu et al 2005). It has already been reported that thermodynamically stable duplexes containing LNA-modified units are active in RNAi-induced gene silencing (Braasch et al 2003;Elmen et al 2005), although their ethylene bridged nucleic acid analogs completely lost their silencing potency (Hamada et al 2002).…”
Section: Duplexes Of Various Lengths With Antisense Strands Fully Modmentioning
confidence: 99%
“…To quantitatively determine in vivo RNAi activity, dual fluorescence reporter systems using EGFP and DsRed (RFP) have been developed and used by many researchers Rana 2002, 2003;Chiu et al 2004Chiu et al , 2005Shah et al 2005;Yang et al 2005). Our assay procedure was established according to the previous reports with some modifications.…”
Section: Fluorescence Measurementsmentioning
confidence: 99%
“…The criterion applied for evaluation of the drugmediated siRNA effects was the ratio of EGFP/RFP fluorescence in the presence of siRNA calculated and normalized to the EGFP/RFP ratio of mock treated cells. Using this assay strategy, two compounds named ATPA-18 and ATPA-21 were identified to specifically inhibit ATP-dependent events occurring during RNAi [31]. A series of in vitro and in vivo analyses demonstrated that these compounds specifically affected an early unwinding step in the RNAi pathway, suggesting that its target is an ATP-dependent RNA helicase, although the precise molecular target remains to be elusive [31].…”
Section: In Vivo Fluorescence-based Report Assay To Monitor the Activmentioning
confidence: 99%
“…Using this assay strategy, two compounds named ATPA-18 and ATPA-21 were identified to specifically inhibit ATP-dependent events occurring during RNAi [31]. A series of in vitro and in vivo analyses demonstrated that these compounds specifically affected an early unwinding step in the RNAi pathway, suggesting that its target is an ATP-dependent RNA helicase, although the precise molecular target remains to be elusive [31]. While these compounds were the first inhibitors for the siRNA activity, they had no effect on the endogenous miRNA pathway, establishing the timing of siRNAs' unwinding and suggesting that siRNA helicase activity is required for RNAi.…”
Section: In Vivo Fluorescence-based Report Assay To Monitor the Activmentioning
confidence: 99%
See 1 more Smart Citation